Nghiên cứu phụ gia chống ăn mòn kim loại trên cơ sở ôxy hóa, nitro hóa dầu khoáng có độ nhớt trung bình - Nguyễn, Mạnh Tường (2020)
Some kinds of corrosion and rust inhibitor, antioxidants and tackiness agents have been synthesized. Based on these additives several rust preventive oil have been formulated and tested.